Factors Affecting Switching Behavior Of Customers In Indian Banking Industry (International Journal of Environmental Sciences, 2025)
This study investigates determinants of customer switching in India’s retail banking sector using an online questionnaire administered to 55 savings-account holders in Rajasthan. The instrument measured nine potential drivers on a five-point Likert scale and captured demographic data. Descriptive statistics identified high monthly average balance requirements and the absence of nearby branches as the most frequently endorsed motives for defection. One-way ANOVA revealed that gender influenced only perceptions of staff behavior (p < 0.05), whereas occupation significantly affected four reasons—high balance requirements, poor recovery from service failure, branch unavailability and low interest rates (p < 0.05). These patterns suggest that switching is multifaceted but ultimately rooted in perceived service shortfalls, underscoring the need for banks to align operational and relational strategies with segment-specific expectations. Findings provide actionable insights for relationship managers seeking to reduce churn and for scholars examining service switching in emerging markets. Future research should validate these patterns with larger samples.